Availing the Amorphous Speaking Partner of Artificial Intelligence: An Attempt to Alleviate Speaking Anxiety - Lestari, Hernina Dewi; Hartatik, Sri Fatmaning; Amalyasari, Maya Rizki (Linguapedia, 2025)
This study aims to describe how the avail of Artificial Intelligence-based ChatGPT as an amorphous speaking partner helps alleviate students’ speaking anxiety. By employing a classroom action research (CAR) method, this study involved 42 students in an English Department class in a private university in Malang. The participants were 32 female students and 10 male students in a Basic English-Speaking class. The researchers employed purposive sampling and chose those forty-two students as the research subjects as they indicated speaking anxiety. The procedure of this research included one cycle of planning, acting, observing, and reflecting. The findings portrayed that the use of chatting through voice in ChatGPT was a great success in alleviating students’ speaking anxiety. The success was reflected on the leap of students’ speaking performance after the utilization of artificial intelligence-based speaking partner. The observation carried out during this study supported the finding as the majority of the students were indicated as more active and confident in performing speaking attempts through ChatGPT compared to when they were required to speak to their peers. Also, the interview with students confirmed that they did not feel pressure when they spoke with ChatGPT as much as when they faced real humans. Thus, the utilization of AI-based ChatGPT voice feature is advised to be used to reduce speaking anxiety in other contexts and subjects.